2020
DOI: 10.1055/s-0040-1707314
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azido Acids and Their Application in the Preparation of Complex Peptides

Abstract: Azido acids are important synthons for the synthesis of complex peptides. As a protecting group, the azide moiety is atom-efficient, easy to install and can be reduced in the presence of many other protecting groups, making it ideal for the synthesis of branched and/or cyclic peptides. α-Azido acids are less bulky than urethane-protected counterparts and react more effectively in coupling reactions of difficult-to-form peptide and ester bonds. Azido acids can also be used to form azoles on complex intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 175 publications
(165 reference statements)
0
1
0
Order By: Relevance
“…Mechanistic studies suggest that this reaction involves Mn-catalyzed alkyl radical formation and subsequent azidyl group transfer through Mn III/IV electrocatalysis, which avoids the oxidation to carbocation thus minimizing the side reactions leading to oxygenated products. In addition to these new research articles, we also found a few new review articles that were published during the manuscript review process. …”
Section: Literature Updates: Additions Made During Manuscript Revisionmentioning
confidence: 99%
“…Mechanistic studies suggest that this reaction involves Mn-catalyzed alkyl radical formation and subsequent azidyl group transfer through Mn III/IV electrocatalysis, which avoids the oxidation to carbocation thus minimizing the side reactions leading to oxygenated products. In addition to these new research articles, we also found a few new review articles that were published during the manuscript review process. …”
Section: Literature Updates: Additions Made During Manuscript Revisionmentioning
confidence: 99%